DA'WAH RHETORIC STRATEGY USTADZ ABDUL SOMAD EPISODE "MAN CLOSEST TO ALLAH" - Rita Silpina; Rhani Febria (SOSIOEDUKASI, 2026)
Da'wah is a form of communication that aims to convey Islamic teachings to the community. In delivering lectures, language has an important role because through the language of da'wah messages can be understood by listeners. One of the linguistic elements that plays a role in the lecture is diction or word selection. The right choice of words can help the speaker convey the message more clearly, engagingly, and persuasively. Therefore, this study aims to describe the use of diction in the lecture delivered by Abdul Somad and explain its contribution in building the rhetorical elements of ethos, pathos, and logos. This research uses a qualitative approach with a content analysis method. The research data in the form of speech contained in a lecture entitled Humans Closest to Allah was uploaded on Ustadz Abdul Somad's YouTube channel. The data collection technique is carried out through the see-and-record method by listening carefully to the lecture and then recording speech that contains the use of diction. The data obtained was then analyzed through the stage of data reduction, classification of diction types, and interpretation of meanings related to rhetorical elements. The results of the study showed that 50 speeches were found that contained the use of diction, namely connotative diction as many as 22 speeches, synonyms of 12 speeches, antonyms of 9 speeches, hyponymy of 6 speeches, and polyemia of 1 speech. Connotative diction is the most dominant type used because it is widely used to convey religious messages symbolically and emotionally. In addition, the results of the study also show the relationship between the use of diction and rhetorical elements, namely logos as many as 23 speeches, pathos 18 speeches, and ethos 9 speeches. These findings show that the choice of diction in lectures has an important role in building the power of da'wah rhetoric so that the message conveyed can be understood, felt, and accepted by the audience more effectively.